2019
DOI: 10.1111/phn.12609
|View full text |Cite
|
Sign up to set email alerts
|

Intention to care for gay and lesbian patients and knowledge about homosexuality: A comparison of Taiwanese nurses in 2005 and in 2017

Abstract: Objective: To examine the differences in the levels of intention to care for gay and lesbian patients and knowledge regarding homosexuality among Taiwanese nurses between 2005 and 2017 and the moderators of these differences. Design and Sample: This two-wave survey study was conducted on nurses in 2005 (N = 1,176; Survey 2005) and 2017 (N = 1,519; Survey 2017) recruited from three hospitals. Measurements: An anonymous self-report questionnaire was used. Results: In Survey 2017, the nurses expressed both a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
2
0
2
Order By: Relevance
“…In particular, young PHC nurses indicated that they fully understand the times they are living in; they also have friends and relatives who are part of the LGBTQI community, and, as a result, it is easier for them to render services to any member of the LGBTQI community. This is in line with another study that indicated that nurse’ experiences and knowledge during care provision for LGBTQI patients for the nurses was moderately influenced and increased by their having LGBTQI friends and relatives [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…In particular, young PHC nurses indicated that they fully understand the times they are living in; they also have friends and relatives who are part of the LGBTQI community, and, as a result, it is easier for them to render services to any member of the LGBTQI community. This is in line with another study that indicated that nurse’ experiences and knowledge during care provision for LGBTQI patients for the nurses was moderately influenced and increased by their having LGBTQI friends and relatives [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…A study conducted in Taiwan examined whether there was a difference between nurses’ willingness to provide care for lesbian and gay people and their knowledge about homosexuality between 2005 and 2017. The study reported that nurses provided care for lesbian and gay people more often, and that there was an increase in friendly attitudes towards them, so it was concluded that nurses’ knowledge about homosexuality and their intention to provide care for lesbian and gay people had changed in a positive way (Lin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the study by Lin et al that the experience of nurses in providing care and having knowledge about members of the LGBTQI community for the nurses was moderately increased and influenced by having LGBTQI friends or relatives. 30 …”
Section: Discussionmentioning
confidence: 99%